Prognostic Values of Baseline 18F-FDG PET/CT in Patients with Peripheral T-Cell Lymphoma. (26th February 2020) - Zhou, Yeye; Zhang, Xiaoyi; Qin, Haifeng; Zhao, Zixuan; Li, Jihui; Zhang, Bin; Sang, Shibiao; Wu, Yiwei; Deng, Shengming
Abstract : Purpose . In the present study, we aimed to investigate whether the metabolic parameters on baseline 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) could be used to predict prognosis in peripheral T-cell lymphomas (PTCL). Methods . A total of 51 nodal PTCL patients who underwent baseline 18 F-FDG PET/CT were retrospectively evaluated in the present study. Total metabolic tumor volume (TMTV), total lesion glycolysis (TLG), and maximum standardized uptake value (SUVmax ) were also assessed. Besides, the National Comprehensive Cancer Network International Prognostic Index (NCCN-IPI) was also included. Log-rank test and Cox regression analysis were used to evaluate progression-free survival (PFS) and overall survival (OS). Results . The median follow-up was 18 months. Patients with low TLG, TMTV, and SUVmax levels had a significantly better clinical outcome than those with high TLG, TMTV, and SUVmax levels. The 2-year PFS rates of the high- and low-TMTV groups were 34.62% and 80%, respectively (p < 0.001 ), whereas the corresponding 2-year OS rates were 46.15% and 84.00%, respectively (p < 0.001 ). The 2-year PFS rates of the high- and low-TLG groups were 29.63% and 87.50%, respectively (p < 0.001 ), whereas the corresponding 2-year OS rates were 40.74% and 91.67%, respectively (p < 0.001 ). In multivariate analysis, TLG and TMTV were independent prognostic factors of both PFS (HR 11.562, 95% CI 3.218-41.542, p < 0.001 and HR 7.061, 95% CI 2.464-20.229, p < 0.001, respectively) and OS (HR 11.609, 95% CI 2.595-51.930, p = 0.001 and HR 5.026, 95% CI 1.538-16.421, p = 0.008, respectively). Moreover, SUVmax and NCCN-IPI scores were also independent predictors of OS (HR 3.161, 95% CI 1.197-8.346, p = 0.020 and HR 3.112, 95% CI 1.109-8.732, p = 0.031, in TMTV multivariate models). Combination of TMTV and NCCN-IPI scores stratified the patients into three risk groups for PFS (p = 0.002 ) and OS (p < 0.001 ) as follows: high-risk group with TMTV > 62.405   c m 3 and NCCN-IPI score of 4-8 (2-year PFS and OS were both 20%, n = 10 ), intermediate-risk group with TMTV > 62.405 or NCCN-IPI score of 4-8 (2-year PFS and OS were 52.4% and 66.7%, respectively, n = 21 ), and low-risk group with TMTV ≤ 62.405   c m 3 and NCCN-IPI score of 0-3 (2-year PFS and OS were 80% and 85%, respectively, n = 20 ). Conclusions . Baseline TMTV and TLG were independent predictors of PFS and OS in PTCL patients, and SUVmax and NCCN-IPI scores were also independent predictors of OS. Moreover, the combination of TMTV and NCCN-IPI scores improved patient risk-stratification at the initial stage and might contribute to the adjustment of the therapeutic regime. This trial is registered with ChiCTR1900025526 .